Microencapsulation of Oils: A Comprehensive Review of Benefits, Techniques, and Applications. Issue 1 (13th November 2015) - Bakry, Amr M.; Abbas, Shabbar; Ali, Barkat; Majeed, Hamid; Abouelwafa, Mohamed Y.; Mousa, Ahmed; Liang, Li
Abstract: Microencapsulation is a process of building a functional barrier between the core and wall material to avoid chemical and physical reactions and to maintain the biological, functional, and physicochemical properties of core materials. Microencapsulation of marine, vegetable, and essential oils has been conducted and commercialized by employing different methods including emulsification, spray‐drying, coaxial electrospray system, freeze‐drying, coacervation, in situ polymerization, melt‐extrusion, supercritical fluid technology, and fluidized‐bed‐coating. Spray‐drying and coacervation are the most commonly used techniques for the microencapsulation of oils. The choice of an appropriate microencapsulation technique and wall material depends upon the end use of the product and the processing conditions involved. Microencapsulation has the ability to enhance the oxidative stability, thermostability, shelf‐life, and biological activity of oils. In addition, it can also be helpful in controlling the volatility and release properties of essential oils. Microencapsulated marine, vegetable, and essential oils have found broad applications in various fields. This review describes the recognized benefits and functional properties of various oils, microencapsulation techniques, and application of encapsulated oils in various food, pharmaceutical, and even textile products. Moreover, this review may provide information to researchers working in the field of food, pharmacy, agronomy, engineering, and nutrition who are interested in microencapsulation of oils.